Manajemen Perencanaan Pembelajaran untuk Kaderisasi Muballigh di Pondok Pesantren Takwinul Muballlighin Yogyakarta - Vivit Nur Arista Putra (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2018)
This study aims to describe the management of lesson-plan in Pondok Pesantren Takwinul Muballighin Yogyakarta. The qualitative descriptive research method is used in conducitng this research. The research subjecs consist of ustadz who is the founder pf the pesantren, two of teaching-learning staff, and six students. The data is collected through interviews, observations, and documentation which is then analysed using interactive model of Milles and Michael Huberman consisting of three concurrent steps, namely data reduction, data display, and deduction. This research found that Pondok Pesantren Takwinul Muballighin Yogyakarta principally prepares the syllabus and the instructional planning as the lesson-plan. However, it has not been well- documented since Pondok Pesantren Takwinul Muballighin Yogyakarta is a non-formal religious education institution in which syllabus and lesson plan is not necessarily be structured like formal education.